Governance and Legal Environment - Grabenwarter, Christoph; Vranes, Erich; Winner, Martin (facultas, 2019)
The purpose of this manual is to introduce students to those key aspects of the legal framework that will be most relevant for their studies in business and economics. Its contents are primarily based on relevant European and international legal standards and, where useful, on a comparison of national legal systems. It is aimed at students enrolled in the new Bachelor's Programme in Business and Economics at Vienna University of Economics and Business (WU) as well as students interested in these issues more generally
[2. Auflage]
Keywords: European legal standards; Führung; Governance; Grabenwarter; Internastional legal standards; Legal Environment; national legal systems; nationale Rechtsordnung; Unternehmensrecht; Vranes; Winner; Wirtschaftsrecht